Brightly woven : the graphic novel - Dragoon, Leigh, 1976- (Disney/Hyperion, 2020)
When a young wizard named Wayland North appears in Sydelle Mirabil's village, he offers her the opportunity to become his assistant. Sydelle eagerly accepts, hoping to see the world, but soon realizes that North has his own reasons for choosing her -- reasons that have something to do with North's enemies and a war that threatens to destroy Sydelle's home.